Prototypic corium oxidation and hydrogen release during the Fuel–Coolant Interaction. (January 2015) - Tyrpekl, Vaclav; Piluso, Pascal; Bakardjieva, Snejana; Nižňanský, Daniel; Rehspringer, Jean-Luc; Bezdička, Petr; Dugne, Olivier
Highlights: We analyzed the prototypic and surrogate corium from several FCI R&D programs. Hydrogen release during the Fuel–Coolant Interaction was identified and quantified. Yield of hydrogen release is linked to the melt composition and debris size. During FCI the U0.52 Zr0.48 O1.63 melt produces ∼3 times more H2 than U x Zr1−x O2.0. Abstract: The article is focused on the hydrogen release by chemical reaction of Fuel and Coolant (FCR) during the molten Fuel–Coolant Interaction (FCI) and its impact on the steam explosion (SE) efficiency. Samples of debris coming from several FCI tests have been characterized by solid-state analytical techniques. Two kinds of tests have been analyzed: (i) Experiments using simulant materials (MISTEE, PREMIX, ECO FCI experiments) and tests using prototypic corium i.e., in the U–Zr–O system (KROTOS experiments). The nonradioactive melts produce during FCI from negligible amounts of hydrogen up to 3.6 g per kg of melt. It was found that UO2 –ZrO2 melt solidifies during FCI into face-centered (Fm3m) crystal cell forming a U1− x Zr x O2+ y solid solution. The oxygen over-stoichiometry of the solid solution is the evidence of FCR and release of hydrogen. A method combining chemical analysis by Energy Dispersive X-ray Spectrometry (SEM/EDS) and X-ray Powder Diffraction (XRD) allowed the determination of the oxygen over-stoichiometry y . Therefore, it has been indirectly estimated how much hydrogen was formed during the chemical reaction between hot corium and water. These data are provided for KROTOS KS2, KS4 and KS5 tests performed in the frame of the OECD/NEA Serena phase-2 project. It has been shown that up to i.e., 4.7 g of H2 per kg of delivered corium melt can be formed by the reaction stoichiometric or sub-oxidized UO2 –ZrO2 melts with water. The oxygen over-stoichiometry of the U1− x Zr x O2+ y debris (initially x = 0.48 for KS2; x = 0.35 for KS4; x = 0.38 and y = −0.37 for KS5) varied between 0.107 ⩽ y ⩽ 0.167. The hydrogen formation during FCI is primarily linked to the melt composition and secondary to the size of the fragmented melt droplets.